Problems and Tools for the Detection of Threats to Personnel Security in the Region - Kuznetsova, Natalia Victorovna; Timofeeva, Anastasia Yuryevna (Economy of Regions, 2016)
The investigation of threats negatively affecting the state and the development of human resources as well as the varieties of security threats is of particular importance in the theory and practice of personnel security measures. The purpose of the article is to identify and classify the ideas of the main threats to personnel security of the region (the research is carried out on the example of the Irkutsk region). On the basis of the content analysis of Russian regulatory legal acts and scientific publications, external and internal threats to personnel security of the region are highlighted. As a result, the list of threats to personnel security of the region consisting of 37 stands is composed. The political, economic, demographic, social, technical and technological, ecological, legal, ethnocultural forms of threats are demonstrated. The authors came to the conclusion that the internal threats to personnel security of the region (first of all socio-economic) are dominant. An assessment of the urgency and relevance of the threats to the personnel security of the region is given. With the use of the technology of the hierarchical factorial analysis, the types of threats (factors of the lowest level) were identified and their influence on the general level of the urgency of personnel security threats (a factor of the highest level) is estimated. It is revealed that legal threats, as well as threats caused by the low labour potential of the region, have the most significant impact on the estimation of the urgency of threats. The study applies the following analysis methods - a content analysis, the analysis of linear and cross-distribution, hierarchical factor and correlation analysis. The analysis is based on the data of the expert survey conducted in the Irkutsk region (2015. To determine the relationship (coherence) of the expert evaluations, the Kendall’s coefficient of concordance is calculated. The received results can be used for studying and identification of the personnel security threats, which are specific for a certain region. They can also be a basis for the forecasting and analysis of the threats to regional personnel security and the development of the methods to respond to them.